2022
DOI: 10.1111/jfs.13023
|View full text |Cite
|
Sign up to set email alerts
|

Sheep and goats are reservoirs of colistin resistant Escherichia coli that co‐resist critically important antimicrobials: First study from Jordan

Abstract: There is a knowledge gap on colistin‐resistant and mobilized colistin‐resistant (mcr) Escherichia coli in sheep and goats worldwide. This study determined the prevalence and antimicrobial resistance of mobilized colistin‐resistant (mcr) E. coli in dairy sheep and goat flocks in Jordan. A total of 948 milk samples were collected from 155 flocks across Jordan. The milk samples were pre‐enriched in MacConkey broth and then plated on MacConkey agar supplemented with 8 mg/l colistin and the presence of mcr‐1 gene i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Imipenem, classified as a carbapenem, plays a crucial role as a last-resort antibiotic, particularly effective against microorganisms capable of producing extended-spectrum b-lactamases. Instances of carbapenem resistance have been documented in livestock, including goats and sheep in Southeast Asia, and Jordan (Khalifa et al, 2021;Obaidat et al, 2023). The resistance to imipenem raises significant concerns in healthcare settings, limiting the efficacy of this vital antibiotic in treating serious infections.…”
Section: Discussionmentioning
confidence: 99%
“…Imipenem, classified as a carbapenem, plays a crucial role as a last-resort antibiotic, particularly effective against microorganisms capable of producing extended-spectrum b-lactamases. Instances of carbapenem resistance have been documented in livestock, including goats and sheep in Southeast Asia, and Jordan (Khalifa et al, 2021;Obaidat et al, 2023). The resistance to imipenem raises significant concerns in healthcare settings, limiting the efficacy of this vital antibiotic in treating serious infections.…”
Section: Discussionmentioning
confidence: 99%
“…Among extended-spectrum β-lactamases (ESBLs) producing Gram-negative bacteria, E. coli is considered the most abundant in host environments representing both an indicator pathogen and a predominant vehicle for resistance transmission in one health context [84,85]. A study published from Jordan in 2022 by Obadiat et al reported small ruminants as reservoirs of colistin-resistant and mcr-1-positive E. coli that exhibit coresistance to critically important antimicrobials [86].…”
Section: Escherichia Colimentioning
confidence: 99%
“…Campylobacter spp., primarily C. jejuni and C. coli, inhabit the gastrointestinal tract of mammals, including goats, sheep, and chickens [86]. Specifically, the foodborne pathogen Campylobacter jejuni, a leading cause of foodborne enteritis, is estimated to account for between 400 and 500 cases of gastroenteritis every year.…”
Section: Campylobacter Sppmentioning
confidence: 99%